2020
DOI: 10.1002/sctm.20-0213
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells in human immunodeficiency virus-infected patients with discordant immune response: Early results of a phase I/II clinical trial

Abstract: Between 15% and 30% of HIV-infected subjects fail to increase their CD4 + T-cell counts despite continuous viral suppression (immunological nonresponders [INRs]). These subjects have a higher morbidity and mortality rate, but there are no effective treatments to reverse this situation so far. This study used data from an interrupted phase I/II clinical trial to evaluate safety and immune recovery after INRs were given four infusions, at baseline and at weeks 4, 8, and 20, with human allogeneic mesenchymal stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Based on their results, intravenous infusions of UC-MSCs were found to be safe and well tolerated during the one-month follow-up period. Clinical studies have shown that MSCs have a good therapeutic effect, but some studies have reported that allogeneic AD-MSC infusions are ineffective at improving immune recovery or reducing immune activation and inflammation in patients with an immune response [ 44 ]. Our study found that a small number of patients still had adverse events greater than grade 3 at the one-month follow-up period after post-menstrual blood-derived MSC transplantation [ 181 ].…”
Section: Current Challenges For Msc-based Covid-19 Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their results, intravenous infusions of UC-MSCs were found to be safe and well tolerated during the one-month follow-up period. Clinical studies have shown that MSCs have a good therapeutic effect, but some studies have reported that allogeneic AD-MSC infusions are ineffective at improving immune recovery or reducing immune activation and inflammation in patients with an immune response [ 44 ]. Our study found that a small number of patients still had adverse events greater than grade 3 at the one-month follow-up period after post-menstrual blood-derived MSC transplantation [ 181 ].…”
Section: Current Challenges For Msc-based Covid-19 Therapiesmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) have the capacity to self-renew and differentiate, and MSC-based therapies have received much attention in both basic medicine and clinical research [42][43][44][45]. MSCs can be acquired from most human tissues, including but not limited to, bone marrow (BM), adipose tissue (AD), umbilical cord (UC), Wharton's jelly (WJ), peripheral blood, menstrual blood, placenta, endometrium, amniotic membrane, amniotic fluid, fetal, dental pulp, urine, liver, lung, spleen, intestine, muscle, and synovium [46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…al showed that UC-MSC therapy can increase the number of circulating naive and central memory CD4 + T-cells and restore HIV-specific IFN-γ and IL-2 production, evidence of systemic immune reactivation post-treatment and did not lead to increased viral loads [ 88 ]. However, in a early phase clinical trial for NIR, MSC infusions were found to not effectly improve immune recovery or reduce immune overactivation [ 89 ]. Supplemental in vivo research is needed to elucidate the effects of MSCs in reactivation of HIV-1 in host microenvironment.…”
Section: Msc Therapy In Human Clinical Trials Of Viral Diseasesmentioning
confidence: 99%
“…In addition to the anti-inflammatory agents, many other therapeutic strategies envisioned to correct immune activation are currently being examined in different studies and more candidates will show up as long as the virus is not eradicated. For example, human mesenchymal stem cell therapy has been carried out in long-term treated immunological non-responders in some early phase studies, yet the efficacy thereof to reduce immune activation and improve immune reconstitution remains controversial due to the sizes of different studies and more individualized approach in such studies [40,41] . The obstacles that we have encountered in HIV-1 cure and functional cure had demonstrated our knowledge limitation of the immunopathogenesis of HIV-1 infection.…”
Section: Tripterygium Wilfordii Hook Fmentioning
confidence: 99%